2020
DOI: 10.1016/j.virol.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of lycorine against Zika virus in vivo and in vitro

Abstract: The emergence and re-emergence of Zika virus (ZIKV), is a cause for international concern. These highly pathogenic arboviruses represent a serious health burden in tropical and subtropical areas worldwide. Despite these burdens, antiviral therapies do not exist, and inhibitors of ZIKV are therefore urgently needed. To elucidate the anti-ZIKV effect of lycorine, we used reverse transcription-quantitative real-time PCR (qRT-PCR), immunofluorescence, Westernwestern blot, and plaque forming assay to analyse viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Meanwhile, the expression level of FLuc is used as the internal control to normalize NLuc activity. Since it was previously reported that lycorine inhibited the ZIKA virus by blocking RdRp activity in the in vitro RNA polymerase assay ( Chen et al, 2020 ), we examined the effect of lycorine on MERS-CoV RdRp activity using the cell-based MERS-CoV RdRp activity reporter assay. First, we evaluated lycorine cytotoxicity in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the expression level of FLuc is used as the internal control to normalize NLuc activity. Since it was previously reported that lycorine inhibited the ZIKA virus by blocking RdRp activity in the in vitro RNA polymerase assay ( Chen et al, 2020 ), we examined the effect of lycorine on MERS-CoV RdRp activity using the cell-based MERS-CoV RdRp activity reporter assay. First, we evaluated lycorine cytotoxicity in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Lycorine was reported to suppress viral RNA replication and viral protein synthesis of poliovirus ( Hwang et al, 2008 ), EV71 virus ( Liu et al, 2011 ) and avian influenza virus H5N1 ( Liu et al, 2011 ). Recently, it was suggested that lycorine could inhibit Zika virus viral RNA synthesis and bind to the Zika RdRp protein ( Chen et al, 2020 ). RdRp of RNA viruses is known to be one of the most important viral proteins for viral RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lycorine also inhibits flaviviruses such as West Nile virus (WNV), dengue virus (DENV), and yellow fever virus; however, a single amino acid substitution in the WNV 2K peptide was sufficient to confer lycorine resistance ( 237 ). In mice models, lycorine also possesses antiviral activity against the Zika virus (ZIKV) and inhibits RNA-dependent RNA polymerase ( 214 ) and, as a consequence, decreases the viral load. This is an important development since currently no vaccine or specific antiviral treatment is approved for ZIKV.…”
Section: Alkaloidsmentioning
confidence: 99%
“…This natural alkaloid has immense therapeutic potential as it has shown high specificity in a very low concentration against several cancers both in vivo and in vitro and against various drug-resistant cancer cells ( Roy et al, 2018 ). Recently, lycorine showed anti-viral activity against the Zika virus in vitro and in vivo ( Chen et al, 2020 ). Giordani et al (2011) studied the cytotoxicity of lycorine against T. vaginalis covering a very broad range of concentrations from 2.5 to 1000 ÎŒM.…”
Section: Resultsmentioning
confidence: 99%